2022
DOI: 10.2147/prbm.s347261
|View full text |Cite
|
Sign up to set email alerts
|

High Social Capital is Associated with Decreased Mental Health Problem Among In-School Adolescents in Eastern Ethiopia: A Cross-Sectional Study

Abstract: Purpose The importance of social capital for adolescent mental health has not been explored in low resource settings like Ethiopia. In this study, we examined the association between social capital and mental health problems among in-school adolescents in Harari Regional State, eastern Ethiopia. Methods A cross-sectional study was conducted among 3227 in-school adolescents of 13–19 years. A multistage sampling was used to select participants. Guided self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…18 19 Low social capital measured at an individual or community level is also associated with depression, although inconsistently. [20][21][22][23][24][25] A limited number of mostly cross-sectional studies have investigated the relevance of social capital in people with diabetes. 26 27 Associations of several social capital domains with patients' quality of life, 27 28 glycaemic control [29][30][31] and self-care capacities 32 33 were observed.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…18 19 Low social capital measured at an individual or community level is also associated with depression, although inconsistently. [20][21][22][23][24][25] A limited number of mostly cross-sectional studies have investigated the relevance of social capital in people with diabetes. 26 27 Associations of several social capital domains with patients' quality of life, 27 28 glycaemic control [29][30][31] and self-care capacities 32 33 were observed.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Research has shown associations with lifestyle factors for social networks,12–15 cognitive or structural social capital9 16 17 and both aspects in parallel 18 19. Low social capital measured at an individual or community level is also associated with depression, although inconsistently 20–25. A limited number of mostly cross-sectional studies have investigated the relevance of social capital in people with diabetes 26 27.…”
Section: Introductionmentioning
confidence: 99%